2020
DOI: 10.4049/jimmunol.1900980
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Limit Pneumococcus-Induced Exacerbation of Lung Fibrosis in Mice

Abstract: The current study has been funded by the Bundesministerium für Bildung und Forschung supporting the German Center for Lung Research (Deutsches Zentrum für Lungenforschung).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Moreover, depletion of Tregs by anti-CD25 antibodies at a late stage increased fibrotic scores and hydroxyproline content in the lungs of bleomycin-treated mice, suggesting a protective role of Tregs in pulmonary fibrosis [ 98 ]. Similarly, Tregs played a protective role against pneumococcus-induced lung fibrosis in mice [ 99 ]. Depletion of Tregs by diphtheria toxin resulted in increased lung collagen deposition, elevated Th1/Th2 cytokine levels and exacerbated infection-induced pulmonary fibrosis [ 99 ].…”
Section: Adaptive Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, depletion of Tregs by anti-CD25 antibodies at a late stage increased fibrotic scores and hydroxyproline content in the lungs of bleomycin-treated mice, suggesting a protective role of Tregs in pulmonary fibrosis [ 98 ]. Similarly, Tregs played a protective role against pneumococcus-induced lung fibrosis in mice [ 99 ]. Depletion of Tregs by diphtheria toxin resulted in increased lung collagen deposition, elevated Th1/Th2 cytokine levels and exacerbated infection-induced pulmonary fibrosis [ 99 ].…”
Section: Adaptive Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%
“…Similarly, Tregs played a protective role against pneumococcus-induced lung fibrosis in mice [ 99 ]. Depletion of Tregs by diphtheria toxin resulted in increased lung collagen deposition, elevated Th1/Th2 cytokine levels and exacerbated infection-induced pulmonary fibrosis [ 99 ]. However, Tregs expansion markedly attenuated pneumococcus-induced fibrosis in mice [ 99 ].…”
Section: Adaptive Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Male C57BL6 mice aged between 8 and 12 weeks at the time point of the first infection were infected once or twice with an intranasal inoculum containing 1–1.5×10 6 CFU S. pneumoniae isolate 89/17 tested for a high macrolide resistance (MIC 256 μg/ml) under ketamine/xylazine anesthesia. S. pneumoniae was grown, as recently described [ 47 ], and CFU contained in the inoculum was determined as described before [ 48 ]. To allow the inoculum to reach the lungs, mice were kept in a vertical position for around 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Moyé and collaborators, in a mice model of IPF, studied the potential role of Tregs in the modulation of infection-driven AE-IPF. They observed that Treg depletion worsened the severity of AE-IPF, whereas IL-2 complex-induced expansion of Tregs leads to an attenuation, suggesting that Tregs could act as a regulator of the immune response during AE-IPF through downregulation of lung inflammatory cytokines, including TNF-α, IL-6, and TGF-β [107]. Finally, AE-ILDs result in acute respiratory failure and severe hypoxemia due to an increased intrapulmonary shunt, with consequent strong activation of the respiratory drive.…”
Section: Severe Exacerbations Of Ildmentioning
confidence: 99%